Shared-Custodial Wallet for Multi-Party Crypto-Asset Management - Yimika Erinle; Yebo Feng; Jiahua Xu; Nikhil Vadgama; Paolo Tasca (Future Internet)
Blockchain wallets are essential interfaces for managing digital assets and authorising transactions within blockchain systems. However, typical blockchain wallets often encounter performance, privacy and cost issues when utilising multi-signature schemes and face security vulnerabilities with single-signature methods. Additionally, while granting users complete control, non-custodial wallets introduce technical complexities and security risks. While custodial wallets can mitigate some of these challenges, they are primary targets for attacks due to the pooling of customer funds. To address these limitations, we propose a chain-agnostic Multi-Party Computation Threshold Signature Scheme (MPC-TSS) shared-custodial wallet with securely distributed key management and recovery. We apply this solution to create a wallet design for wealth managers and their clients, consolidating the management and access of multiple cryptocurrency tokens and services into a single application interface.